Возможная патогенетическая роль грибковой инфекции при болезни Паркинсона и паркинсонизме = Fungal infection possible pathogenic role in Parkinson disease and parkinsonism - Gertsev, V. V.; Muratova, T. N.; Vastyanov, R. S.; Stoyanov, A. N. (Journal of Education, Health and Sport, 2015)
Gertsev V. V., Muratova T. N., Vastyanov R. S., Stoyanov A. N. Возможная патогенетическая роль грибковой инфекции при болезни Паркинсона и паркинсонизме = Fungal infection possible pathogenic role in Parkinson disease and parkinsonism. Journal of Education, Health and Sport. 2015;5(3):68-78. ISSN 2391-8306. DOI: 10.5281/zenodo.16247 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A68-78 https://pbn.nauka.gov.pl/works/547948 http://dx.doi.org/10.5281/zenodo.16247 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. УДК 616/617.7 + 612.017.1: 616-056.3 ВОЗМОЖНАЯ ПАТОГЕНЕТИЧЕСКАЯ РОЛЬ ГРИБКОВОЙ ИНФЕКЦИИ ПРИ БОЛЕЗНИ ПАРКИНСОНА И ПАРКИНСОНИЗМЕ FUNGAL INFECTION POSSIBLE PATHOGENIC ROLE IN PARKINSONIAN DISEASE AND PARKINSONISM В. В. Герцев, Т. Н. Муратова, Р. С. Вастьянов, А. Н. Стоянов V. V. Gertsev, T. N. Muratova, R. S. Vastyanov, A. N. Stoyanov Одесский национальный медицинский университет Odessa National Medical University Abstract The critical review of scientific data and own statement concerning a fungal infection possible pathogenetic role in Parkinsonian disease and parkinsonism is given. Authors are based on the numerous clinical observation results which confirm that the fungal infection (mainly of the Candida species) is considered in aspect of its pathogenetic importance in the abovementioned pathology. The data about both fungal-induced striatal damage and dopaminergic striato-nigral neurotransmission failure are interesting that represents the main link of Parkinsonian disease and parkinsonism pathogenesis. Comparing data of clinical works authors emphasize a community of candidosis and parkinsonian clinical manifestations that confirms additionally by these diseases clinical manifestation improvement after antifungal preparations and levadopa treatment. Authors conclude that revealed interrelation between a fungal infection and Parkinsonian disease and parkinsonism allows to consider confidently about the functional pallido-striato-nigral system failure additional pathogenetic link in the form of fungal infection and fungal-induced nervous system intoxication. Key words: fungal infection, candidosis, Parkinsonian disease, pathogenetic mechanisms. Резюме Представлен критический обзор данных научной литературы, а также собственные положения, касающиеся возможной патогенетической роли грибковой инфекции при болезни Паркинсона и паркинсонизме. Авторы основываются на результатах многочисленных клинических исследований, которые свидетельствуют в пользу того, что грибковая инфекция (преимущественно грибы роды Candida) рассматривается в аспекте её патогенетического значения при вышеуказанной патологии. В этом отношении интересны данные о фунгально-индуцированном поражении стриатума, дофаминергической стриато-нигральной нейропередачи, что представляет собой основное звено патогенеза болезни Паркинсона и паркинсонизма. Сопоставляя данные клинических работ, авторы подчеркивают общность клинических проявлений кандидоза и паркинсонизма, что дополнительно подтверждается улучшением клинического течения этих заболеваний вследствие назначения противогрибковых препаратов и левадопы. Авторы заключают, что продемонстрированная взаимосвязь между грибковой инфекцией и наличием болезни Паркинсона и паркинсонизмом позволяет с уверенностью полагать наличие дополнительного патогенетического звена функционального поражения паллидо-стриато-нигральной системы в виде наличия грибковой инфекции и развития фунгальной интоксикации нервной системы. Ключевые слова: грибковая инфекция, кандидоз, болезнь Паркинсона, патогенетические механизмы. Резюме Подано критичний огляд даних наукової літератури, а також власні положення, що стосуються можливої патогенетичної ролі грибкової інфекції при хворобі Паркінсона та паркінсонізмі. Автори грунтуються на результатах численних клінічних досліджень, які свідчать на користь того, що грибкова інфекція (переважно гриби роду Candida) розглядається в аспекті її патогенетичного значення за умов вищевказаної патології. У цьому відношенні цікавими постають дані про фунгально-індуковане ураження стріатуму, дофамінергічної стріато-нігральної нейропередачі, що є провідною ланкою патогенезу хвороби Паркінсона і паркінсонізму. Зіставляючи дані клінічних робіт, автори підкреслюють спільність клінічних проявів кандидозу і паркінсонізму, що додатково підтверджується покращенням клінічного перебігу цих захворювань внаслідок призначення протигрибкових препаратів і левадопи. Автори висловлюють, що висвітлений взаємозв’язок між грибковою інфекцією і наявністю хвороби Паркінсона і паркінсонізмом дозволяє з упевненістю вважати наявність додаткової патогенетичної ланки функціонального ураження палідо-стріато-нігральної системи у вигляді наявності грибкової інфекції і розвитку фунгальної інтоксикації нервової системи. Ключові слова: грибкова інфекція, кандидоз, хвороба Паркінсона, патогенетичні механізми.